Upconversion Luminescence Based Direct Hybridization Assay to Detect Subfemtomolar miR-20 a DNA Analogue in Plasma - Kuusinen, Saara; Lahtinen, Satu; Soukka, Tero (Pergamon Press, 2025)
MicroRNAs (miRNAs) are promising biomarkers especially for early-stage cancer diagnostics, but the implementation of miRNA-based diagnostic tests is still hindered by the limitations of current analytical methods. The small size, low concentrations in biofluids and high sequence homology of miRNAs are challenges for assay development. Currently, most of the sensitive detection methods rely on enzymatic amplification steps, which complicate the analysis and can lead to biases in quantitation. Therefore, there is an increasing need to develop enzyme-free detection methods that are sensitive, specific and user-friendly. In this study, a simple direct hybridization assay for the DNA analogue of miR-20a was developed. The assay is based on upconverting nanoparticle labels, which enable ultrasensitive detection, and hairpin structured probes, which provide additional hybridization stability due to base stacking. The limit of detection was 0.73 fM with plasma recoveries between 76\% and 111\%, demonstrating that the assay could be used for direct detection of miRNAs from complex sample matrices without isolation of RNA. Due to the simplicity and the excellent sensitivity for an amplification-free method, the assay has a great potential for miRNA-based clinical applications.